The effect of chitosan and PEG polymers on stabilization of GF-17 structure: A molecular dynamics study. (1st June 2020) - Asadzadeh, H.; Moosavi, A.; Arghavani, J.H.
Highlights: Chitosan polymers have more ability to interacts with GF-17 than the PEG polymers. the van der Waal energy has more contribution among other types of energies in the interactions of GF-17 with polymers. Chitosan polymers have more ability to conserve the helical structure of GF-17 than PEG polymers. Chitosan could be a more suitable candidate for encapsulation GF-17 rather than the PEG. Abstract: We examine the interactions of chitosan and polyethylene glycol (PEG) with antimicrobial peptide GF-17 to identify a suitable carrier to improve the peptide drug delivery systems. To this end, the molecular dynamics simulations are used to determine the interactions of a typical antimicrobial peptide GF-17 with the chitosan and PEG polymers. The findings indicate the great potential of the peptide to maintain its secondary structure in the adjacent to chitosan polymers. During the interaction with chitosan polymers, the structure of the peptide has smaller fluctuations compared to the PEG polymers. Also, in the presence of both the polymers, the PEG polymers are situated closer to the peptide than chitosan polymers. Moreover, the analysis indicates that the acidic residues and phenylalanine play a crucial role in peptide-polymer interactions. This research provides a valuable insight into the design of polymer surfaces for drug delivery applications such as controlled-release peptide delivery systems.